2021
DOI: 10.1051/0004-6361/202040059
|View full text |Cite
|
Sign up to set email alerts
|

The VANDELS ESO public spectroscopic survey

Abstract: VANDELS is an ESO Public Spectroscopic Survey designed to build a sample of high-signal-to-noise ratio, medium-resolution spectra of galaxies at redshifts between 1 and 6.5. Here we present the final Public Data Release of the VANDELS Survey, comprising 2087 redshift measurements. We provide a detailed description of sample selection, observations, and data reduction procedures. The final catalogue reaches a target selection completeness of 40% at iAB = 25. The high signal-to-noise ratio of the spectra (above … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…For the SXDF field we supplement the GOGREEN redshifts with data from UDSz (Bradshaw et al 2013;McLure et al 2013), the XMM-Large Scale Structure (XMM-LSS) survey (Chiappetti et al 2013;Melnyk et al 2013), and VANDELS (Garilli et al 2021). 3D-HST data are again used only for debiasing the photometric redshifts.…”
Section: B1 Spectroscopymentioning
confidence: 99%
“…For the SXDF field we supplement the GOGREEN redshifts with data from UDSz (Bradshaw et al 2013;McLure et al 2013), the XMM-Large Scale Structure (XMM-LSS) survey (Chiappetti et al 2013;Melnyk et al 2013), and VANDELS (Garilli et al 2021). 3D-HST data are again used only for debiasing the photometric redshifts.…”
Section: B1 Spectroscopymentioning
confidence: 99%
“…The latest VANDELS data release, DR4 (Garilli et al 2021) 2 contains spectra of ∼ 2100 galaxies in the redshift range 1.0 < 𝑧 < 7.0, with on-source integration times ranging from 20 to 80 hours, where > 70% of the targets have at least 40 hours of integration time. The survey depths have been chosen so that the final spectra have high signal-to-noise ratios (SNRs), enabling detailed absorption and emission line studies, the study of ionising sources using emission line ratios, the derivation of accurate metallicities and better constraints on physical parameters such as stellar masses and star-formation rates.…”
Section: Vandelsmentioning
confidence: 99%
“…VANDELS (M18; Pentericci et al 2018;Garilli et al 2021) is a large ESO public spectroscopic survey of the high-redshift Universe, using the VIsible Multi Object Spectrograph (VIMOS) instrument on the Very Large Telescope (VLT). The primary aim of VANDELS is to detect continuum emission at high SNR for high-redshift galaxies, moving beyond redshift acquisition to study galaxy physical properties within the first 5 billion years prior to 𝑧 = 1.…”
Section: Vandels Data and Sample Selectionmentioning
confidence: 99%
“…Spectroscopic redshifts were measured by the VANDELS team using the pandora.ez software (Garilli et al 2010). Spectra were assigned redshift quality flags following Le Fèvre et al (2013), with all but 12 of the 281 observed massive quiescent galaxies assigned quality flags 3 or 4, corresponding to 95 and 100 per cent probabilities of correct identification respectively (in fact, Garilli et al 2021 demonstrate ∼ 99 per cent reliability for the VANDELS flag 3 and 4 redshifts combined). The 12 spectra with lower quality flags, as well as one low-redshift interloper, were excluded from this work, leaving 268 spectra.…”
Section: Vandels Spectroscopic Observationsmentioning
confidence: 99%
See 1 more Smart Citation